2013
DOI: 10.1007/s00268-013-2398-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Current Perioperative Practice in Hepatic Surgery Based on Enhanced Recovery After Surgery (ERAS) Principles?

Abstract: Perioperative care among centers that perform liver resections varied substantially. In current HPB surgical practice, some elements of the ERAS program, e.g., preoperative counselling and minimal fasting, have already been implemented. Elements in the perioperative phase (avoidance of drains and nasogastric tube) and postoperative phase (early resumption of oral intake, early mobilization, and use of recovery criteria) should be further optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 61 publications
(66 reference statements)
2
34
1
6
Order By: Relevance
“…Our management of patients undergoing HBP surgery incorporated a small proportion of evidence-based components described in ERAS programmes for hepatic4 and pancreatic22 surgery. For every eight patients undergoing major HBP surgery, one was at risk of failing enhanced recovery protocols in major HBP surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our management of patients undergoing HBP surgery incorporated a small proportion of evidence-based components described in ERAS programmes for hepatic4 and pancreatic22 surgery. For every eight patients undergoing major HBP surgery, one was at risk of failing enhanced recovery protocols in major HBP surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In order to deepen this issue, a recent report by Wong et al [ 17 ] was developed to assess adhesion to ERAS principles in 11 hepatobiliary centers in Europe: "Compliance" of centers was defi ned according to fulfi llment of 22 ERAS protocol core items. The author observed that the median number of implemented items per center was 9 and compliance was partial in preoperative and perioperative phases, while it was still poor during postoperative course, so they concluded that implementation of fasttrack protocols is desirable in order to standardize care and improve recovery after surgery even further, but it requires multidisciplinary efforts.…”
Section: Results Of Fast-track Programs In Liver Surgerymentioning
confidence: 99%
“…Harmonization and implementation of multimodal enhanced recovery programs in liver surgery [8] might further improve patient care and validity of prospective (single-multicentre) observational clinical studies.…”
mentioning
confidence: 99%
“…Reduced preoperative red blood cell count was reported as an independent risk factor for 80-months mortality in 758 patients undergoing hepatic resection for primary liver cancer [7]. Backbleeding during laparoscopic liver surgery might be well controlled by a CO 2 pneumoperitoneum at 10e14 mmHg and a central venous pressure at <5 mmHg [2,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation